Uji Efektivitas Agen Hayati Dari Rizosfer dan Filosfer Tanaman Solanaceae untuk Mengendalikan Penyakit Antraknosa pada Tanaman Cabai Rawit (Capsicum frutescens L.) - NAPITUPULU, HENRI PAN BAGUS MULIA; KHALIMI, KHAMDAN; SUPRAPTA, DEWA NGURAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.9, No.1, Januari 2020, 2020)
Effectiveness of biological agents from Solanaceae plants rhizosphere and filosphere to control Antrachnose disease in Chili Pepper Plants (Capsicum frutescens L.). The disease antrachnose caused by the fungus Colletotrichum truncatum can attack the chili fruit at any stage, but it will not attack the leaves or stems. The use of biological agents from the rhizosphere and filosphere is a viable alternative to control the anthracnose disease. Biological agents work selectively and better for the ecosystem. The goal of this research is to identify the effectivenes of biological agents from rhizospheres and filospheres solanaceae plant to control C. truncatum that causes antrachnose disease in Chili Pepper Plants (Capsicum frutescens L.). This research takes place in vitro and the field this research shows that TmFr4 and TrRr7 treatment can inhibit the growth of C. truncatum in vitro with a high percentage of inhibition 90,58 % and 91,23 %. The TrRr7 bacterial isolate can inhibit the anthracnose disease from 95,23% to 64,23 % and able to reduce the intensity from 66,59 % tob 39,06 % while TmFr4 fungal isolates can inhibit the desiase from 95,23 % to 68,81 % and reduce its intensity from 66,59 % to 47,03 % base on the field test. Further study is needed to analyze the stability of TmFr4 fungal isolate and TrRr7 bacterial isolate biological control of C. truncatum in the field.